Transforming Images: The Art of Silver Horn and His Successors - Berlo, Janet Catherine; Donnelley, Robert G; Green, Candace S (David and Alfred Smart Museum of Art, University of Chicago, 2001)
Silver Horn's art documents the changes in the lives of the Kiowa Indians, as well as changes in Kiowa art itself. The art presented here, shows the bridge he created between ancient Kiowa aesthetics and modern forms of expression that had an impact on younger Native American artists.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé